Patient Satisfaction of Outpatient Gastroscopy in Universiti Malaya Medical Centre Endoscopy Unit - Ahmad Najib Azmi; Wah-Kheong Chan; Shiaw-Hooi Ho; Khean-Lee Goh (Wiley-Blackwell, 2024)
Indexed by WOS